2014
DOI: 10.5713/ajas.14.0418
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Serum Calcium Concentration, Frequency of Ruminal Contraction and Feed Intake Soon after Parturition of Dairy Cows Fed Difructose Anhydride III

Abstract: Requirements to control the large decrease in serum calcium (Ca) due to parturition and to increase the feed intake soon after parturition have been well accepted in dairy cows. This study was aimed to investigate the feed intake affected by serum Ca concentration with difructose anhydride (DFA) III supplement in dairy cows soon after parturition. Fourteen transition Holstein cows were divided into DFA and control (CONT) groups within 1 to 5 parity variations in each group. Measurement schedule for an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…The average DMI during the first week after calving was positively associated with the serum Ca concentration immediately after calving ( p < .01). This result agreed with those obtained by Wynn et al () and Reshalaitihan and Hanada (). Wynn et al () demonstrated that serum Ca concentration during the first week after calving was positively associated with the rumen contraction frequency and the DMI after calving.…”
Section: Discussionsupporting
confidence: 94%
“…The average DMI during the first week after calving was positively associated with the serum Ca concentration immediately after calving ( p < .01). This result agreed with those obtained by Wynn et al () and Reshalaitihan and Hanada (). Wynn et al () demonstrated that serum Ca concentration during the first week after calving was positively associated with the rumen contraction frequency and the DMI after calving.…”
Section: Discussionsupporting
confidence: 94%
“…As known decreased Ca +2 levels a few days before calving is quite a little at 12-24 hours after calving and get back to normal levels until three to four days later (Goff, 2008;Martinez et al, 2012). Considering to Ca +2 levels are lowest at postpartum first two days (Goff, 2008) and increase after postpartum 3rd day (Martinez et al, 2012), postpartum increased Ca +2 levels in our study may be explained with the feeding of dairy cows after calving, development of ruminal contraction (Wynn et al,2015) and with postpartum blood analysis performed at 1st and 2nd weeks not first 2 days in our study.…”
Section: Discussionsupporting
confidence: 63%
“…Cows with low serum Ca concentrations showed inactive digestive tract motility (Goff, ). Wynn, Teramura, Sato, and Hanada () demonstrated that serum Ca concentrations after calving were positively associated with the rumen contraction frequency and DMI after calving. Although there was no significant difference in the serum Ca concentration at 3 days after calving between the first lactation heifers and the multiparous cows, the serum Ca concentration generally tends to be low in high parity cows (Teramura et al., ; Wynn et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Wynn, Teramura, Sato, and Hanada () demonstrated that serum Ca concentrations after calving were positively associated with the rumen contraction frequency and DMI after calving. Although there was no significant difference in the serum Ca concentration at 3 days after calving between the first lactation heifers and the multiparous cows, the serum Ca concentration generally tends to be low in high parity cows (Teramura et al., ; Wynn et al., ). First lactation heifers can maintain serum Ca at steady concentrations without any treatments after calving because low parity cows absorb Ca efficiently, owing to active mechanisms of Ca homeostasis, including Ca absorption from the intestine and bone resorption (Bronner, ; Goff, Reinhardt, & Horst, ; Kamiya, Kamiya, Tanaka, & Shioya, ).…”
Section: Resultsmentioning
confidence: 99%